The Conquest of Nuwakot: A Study in Military Excellence (1744 AD) (Unity Journal, 2025)
The victory over Nuwakot marked the first significant step in the unifi cation campaign of Nepal. Strategy is a policy or plan utilized during wartime to get success in operations. Throughout history, kings and warriors have employed various strategies to get victory in warfare. In this context, King Prithvi Narayan Shah implemented several strategies to get victory over Nuwakot. Under his leadership, multiple strategies were executed to achieve this significant milestone. So, the problem statement of this paper is to analyze the military strategies adopted by Gorkhali Forces to ensure success in Nuwakot. Key strategies used during the attack on Nuwakot included launching assaults from multiple directions to disrupt and weaken the Malla forces. The soldiers disguised themselves as farmers to launch a surprise attack, which was strategically timed at first light during the rainy season. Prithvi Narayan Shah persuaded local fishermen to build boats by offering them land to cross the Trishuli River. After the first setback, the Gorkhali forces retreated, destroying the bridge and boats to hinder any subsequent counterattack. The objective of this study is to provide a comprehensive analysis of the military strategies employed in the conquest of Nuwakot and to evaluate the effectiveness of these strategies in achieving the intended goal. The study also aims to assess the impact of these strategies on the overall unification campaign of Nepal. Methodologically, this study employs a qualitative research approach. Primary and secondary sources are used to provide context and support the findings.